Education influences the role of genetics in myopia - Verhoeven, Virginie J. M. (Springer Netherlands, 2013)
Myopia is a complex inherited ocular trait resulting from an interplay of genes and environmental factors, most of which are currently unknown. In two independent population-based cohorts consisting of 5,256 and 3,938 individuals from European descent, we tested for biological interaction between genetic predisposition and level of education on the risk of myopia. A genetic risk score was calculated based on 26 myopia-associated single nucleotide polymorphisms recently discovered by the Consortium for Refractive Error and Myopia. Educational level was obtained by questionnaire and categorized into primary, intermediate, and higher education. Refractive error was measured during a standardized ophthalmological examination. Biological interaction was assessed by calculation of the synergy index. Individuals at high genetic risk in combination with university-level education had a remarkably high risk of myopia (OR 51.3; 95 % CI 18.5–142.6), while those at high genetic risk with only primary schooling were at a much lower increased risk of myopia (OR 7.2, 95 % CI 3.1–17.0). The combined effect of genetic predisposition and education on the risk of myopia was far higher than the sum of these two effects (synergy index 4.2, 95 % CI 1.9–9.5). This epidemiological study provides evidence of a gene-environment interaction in which an individual’s genetic risk of myopia is significantly affected by his or her educational level. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10654-013-9856-1) contains supplementary material, which is available to authorized users.